Contralateral Anterior Interhemispheric–Transcallosal–Transrostral Approach for the Resection of a Subcallosal Cavernous Malformation: A Case Report and an Operative Video - Costa Alves, Aderaldo; Zanini, Marco Antônio; Hamamoto Filho, Pedro Tadao; Chaddad-Neto, Feres Eduardo Aparecido (Frontiers in Surgery, 2022)
This case report demonstrates the surgical resection of a cerebral cavernous malformation located in the subcallosal region. The authors present a detailed operative video explaining the steps to successfully remove the lesion trough a contralateral interhemispheric-transcallosal-transrostral approach, with the patient in lateral decubitus. The surgical procedure was uneventful and the patient had no postoperative deficits and no residual lesion in a 3-month follow-up.